New Insights in Stability, Structure and Properties of Porous Materials - Annalisa Martucci (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Porous materials (such as zeolites, clay minerals, and assemblies of oxide nanoparticles) are of great importance for the progress of many technological and environmental fields, such as catalysis, adsorption, separation, and ion exchange, because of their unique pore topologies, tunable structures, and the possibility of introducing active reaction sites. The major goal of this Special Issue was to provide a platform for scientists to discuss new insights in the stability, structure, and properties of porous materials, as well as in innovative aspects of their processing and applications. The emphasis was given as the relationships between the structure and/or chemical composition and the specific physical properties of these materials, as well as their role in mineralogical, technological, green, and sustainable processes. In this Special Issue of Minerals, we provide an up-to-date selection of high-quality original and review papers concerning the physical, chemical, and structural characterization of porous materials, the synthesis of crystalline phases with pores in the appropriate range, structure-property relationships at ambient conditions, but also at high temperatures and/or at high pressures, adsorption, and diffusion of mobile species in porous materials, host-guest interactions and confinement effects, ion exchange, modeling in geological and environmental processes, and new insights in processing and applications. In total, eight topical contributions reflect both the diversity and interdisciplinary of modern mineralogy, bridging together experimentalists and computational approaches.